The Conception of the Fatherland Dishonored by Captivity in the Ukrainian Poetic History and Philosophy - GOLOD, ROMAN (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
In the article, an analysis of the conception of the Fatherland dishonored by the captive colonial status is provided with regard to the artistic work of the Ukrainian poets. The feeling of shame, rage and hatred towards the enslaved Ukraine is more or less seen in the historic and philosophic views of T. Shevchenko, P. Kulish, I. Franko, L. Ukrainka, I. Malaniuk. The prominent poets have always been playing the role of ‘nerves’, indicators of the political, social, cultural and moral health of the people. So the conception of shame for the captivated Ukraine in their artistic work should be viewed as the determinant for the further nation recovery.